TPP (Trans-Pacific Partnership) and Digital Copyright Infringement (Conflict Interest between Japan, USA, and Indonesia) - Bayu Sujadmiko (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
Japan and the United States are sample countries, which have effectively control to reduce the number of illegal file sharing. They attempt to create a healthy Internet environment by promoting the Trans-Pacific Partnership (TPP). However, not all the members and its domestic parliaments agree with the whole provisions, specifically on Intellectual Property Chapter. Though, they keep strain to invite other nations to join the treaty. Indonesia agreed with the virtuous purposes of TPP, but it is too fast for Indonesia to ratify into domestic regulation. Indonesia is not ready yet to face the global market with low-potency. The article will show what the interest of both countries behind the TPP agreement is. It also describes how domestic copyright regulation touches illegal file sharing practices. Keywords: TPP, illegal file sharing, enforcement